Chronic granulomatous disease in the United Arab Emirates: clinical and molecular characteristics in a single center - Al Kuwaiti, Amna Ali; Al Dhaheri, Ahmed Darwaish; Al Hassani, Moza; Ruszczak, Zbigniew; Alrustamani, Ahmad; Abuhammour, Walid; El Ghazali, Gehad; Al-Hammadi, Suleiman; Shendi, Hiba M. (Frontiers in Immunology, 2023)
Background Chronic granulomatous disease (CGD) is a genetic disorder caused by defective oxidative burst within phagocytes, manifesting as recurrent, severe infections as well as hyperinflammation. Objective This is the first report from the United Arab Emirates (UAE) to describe the demographic, clinical, laboratory, radiological, and genetic characteristics of patients with CGD. Methods This is a retrospective study that was conducted at Tawam Hospital in the UAE on patients with confirmed CGD between 2017 and 2022. Results A total of 14 patients were diagnosed with CGD, of whom 13 patients had autosomal recessive (AR) CGD due to NCF1 deficiency. Consanguinity was noted in all patients with AR CGD, whereas positive family history was identified in 50% of cases. The median age of onset of symptoms was 24 months, while the median age at diagnosis was 72 months. Lymphadenitis was the most common clinical feature identified in 71% of patients. Other common infectious manifestations included abscess formation (57%), pneumonia (50%), invasive aspergillosis (21%), oral thrush (14%), and sepsis (14%). Disseminated trichosporonosis was reported in one patient. Autoimmune and inflammatory manifestations included celiac disease in two patients, diabetes mellitus and asymptomatic colitis in one patient each. Genetic analysis was performed in all patients; NCF1 deficiency was diagnosed in 13 (93%) patients, with c.579G>A being the most prevalent pathogenic variant identified. The treatment modalities, as well as treatment of acute infections, treatment modalities included antimicrobial prophylaxis in 12 (86%) patients and hematopoietic stem cell transplant in six patients (42%). Conclusion This is the first report from the UAE describing the clinical and molecular characteristics of patients with CGD. The homozygous variant c.579G>A causing NCF1 deficiency can be considered as a founder mutation for AR CGD in the UAE.